THE CONCEPT OF "HOSPITALITY" IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES LINGUISTIC AND CULTURAL CHARACTERISTICS OF EXPRESSIVE PROVERBS - Khamrokhonova Sokinakhan Jurakhonovna (Web of Journals Publishing, 2024)
In the second half of the twentieth century, English, Uzbek and Russian scholars have been interested in the linguistic and cultural analysis of the concept of hospitality. A lot of work has been done in the field of English. There are many theoretical literatures in this regard. Linguistic and cultural features of proverbs are also emphasized. In short, proverbs are one of the most studied areas.
Keywords: Semantics, concept of hospitality, national-cultural semantics, phraseological unit, etymological.